Kantor Virtual dan Keseimbangan Kehidupan-Kerja bagi Generasi Z dan Pengusaha di Indonesia - Rachma, Nayla; Reka Pramesti Dwilingga Kartiwa; Chaniago, Harmon (International Journal Administration, Business & Organization, 2025)
The post-pandemic era has brought a major transformation in work models, accelerating the adoption of virtual offices, particularly among Generation Z and young entrepreneurs in Indonesia. This phenomenon raises questions about whether flexible work settings truly support work-life balance or pose new psychological and operational challenges. This study aims to explore the role of virtual offices in facilitating work-life balance and identify the main obstacles in their implementation. Using a qualitative-descriptive literature review method, data were synthesized from peer-reviewed journals, national reports, and relevant online publications. The analysis shows that virtual offices offer significant benefits, such as reduced operational costs, increased autonomy, and improved job satisfaction. These advantages align well with the digital-native traits and flexibility preferences of Generation Z. However, challenges such as blurred work-life boundaries, digital fatigue, and limited emotional engagement remain prominent. To address these issues, several strategies are proposed, including structured digital communication policies, wellness programs, and virtual team-building initiatives. The study concludes that while virtual offices provide a promising solution for sustainable and flexible work culture, their effectiveness relies heavily on digital discipline, cultural adaptation, and strategic management. The findings offer practical insights for young professionals and entrepreneurs who aim to optimize virtual office systems while maintaining productivity and well-being in the evolving Indonesian business environment.